The TMA team and TTP pathway improved outcomes in a cohort with Thrombotic thrombocytopenic purpura - Samuel A. Merrill; Stephen Yu; Sylvia E. Webber; John Gotses; Emma L. Platt; Ruta Arays; Aaron D. Shmookler (PLoS ONE, 2025)
Background Providing optimal care for patients with thrombotic thrombocytopenic purpura (TTP) is challenging because of multiple involved specialties, knowledge gaps, and a high rate of disease relapse. A thrombotic microangiopathy (TMA) Team and TTP Pathway could improve outcomes. Objectives To assess if a structured TTP Pathway, supported by a TMA Team, improved TTP care by reducing TTP relapse and TTP-related death (TTP-RRD) at a rural Appalachian medical center. Methods Prospective cohort quality improvement project using the DMAIC quality improvement framework (Define, Measure, Analyze, Improve, Control) to develop a TMA Team and TTP Pathway. Pathway care included standardized use of therapeutic plasma exchange (TPE), rituximab, caplacizumab, as well as improved coordination between medical services, and regular outpatient biochemical TTP surveillance. Outcomes were determined by retrospective chart review for patients with acute TTP treated with usual care (N = 16 episodes) and the TTP Pathway (N = 16 episodes). Results and conclusions All patients had acquired TTP. TTP-RRD at 90 days was reduced from 69% with usual care to 6% with Pathway care (95% CI 0.35 to 0.90, P = 0.0004), a relative risk reduction of 91%; TTP relapse alone at 90 days was reduced from 62% to 0% (95% CI 0.36 to 0.88, P = 0.0002) with Pathway care. The number needed to treat to prevent TTP-RRD was 1.59 at 90 days. Over the project duration usual care demonstrated a hazard ratio for TTP-RRD of 12.58 compared to Pathway care. With the intervention, the duration of TPE was increased (median 6 vs 12 sessions, P < 0.05), as was use of rituximab (31.3% vs 93.8%, 95% CI −0.36 to −0.88, P = 0.003), and caplacizumab (6.3% vs 62.5%, 95% CI −0.027 to −0.81, P = 0.001). All Pathway patients underwent biochemical surveillance, and 31% had pre-emptive rituximab to reduce possibility of clinical relapse. A structured TTP Pathway significantly reduces morbidity and aligns care with modern clinical guidelines. The TMA Team is a valuable institutional resource to improve outcomes.